The Effect of Ukrainian Refugees on the Local Labour Markets: The Case of Czechia - Agnieszka Postepska; Anastasiia Voloshyna (Institute of Labor Economics (IZA), 2024)
Following the Russian Federation's invasion of Ukraine on 24th February 2022, over a quarter of the Ukrainian population became displaced, with many seeking refuge across Europe. Czechia emerged as a key destination, granting Temporary Protection to approximately 433 thousand Ukrainians by the end of 2022, thus sheltering the highest per capita number of Ukrainian refugees worldwide. The swift enactment of the Lex Ukraine Act granted the refugees benefits typically reserved for permanent residents, such as unrestricted access to the labour market. This led to a notable increase in the number of Ukrainians officially employed and expanding Czechia's workforce. Using individual micro-level data from sixteen waves of the Labour Force Sample Survey (LFSS), collected between the 1st quarter of 2019 and the 4th quarter of 2022, we examine the short-term impact of the influx of the Ukrainian refugees on the labour market outcomes of locals in Czechia. Using several empirical strategies, including a two-way fixed effects model (TWFE), extensions to the canonical difference in differences (DiD) estimator, and matching on selective characteristics of individuals/districts and pre-treatment trends, we find consistent evidence that the influx of refugees had no economically meaningful impact on employment, unemployment, or inactivity rates within the local population, regardless of gender, educational level, or industry, noting that we find small negative effects on employment and positive effects on unemployment in sectors that experienced the largest influx of workers. However, we treat these results with caution due to the small sample sizes. Most importantly, we find consistent evidence of an increase in weekly working hours among local females in treated districts. This increase is primarily driven by workers with secondary education employed in the most affected sectors.
Keywords: F22; J15; J21; 330; Ukrainian refugees; immigrants; local labour market; labour supply